Comparison of electric field distribution for different power transformer designs - Keshanraj A/L Balakrishnan (2023)
The main objective of this research is to design a power transformer which provides improvement in electric field distribution compared to the existing power transformer. FEM calculation tool is introduced to calculate the maximum electric field of the existing power transformer and newly designed power transformer. Both the transformers are constructed in the FEM simulation tool. The existing power transformer design consists of HV coil, LV coil, transformer oil and baffle plate in between the insulation of HV coil and LV coil. While the newly design power transformer consists of HV coil, LV coil, transformer oil and an angle ring on the HV side attached to the baffle plate. Electric field of both power transformer is calculated and observed by varying the coil to yoke distance and the main insulation width.